A method to estimate the damage of Diabrotica speciosa larvae on potato tubers - Barboza,Marcos Roberto (2021)
ABSTRACT The marketable value of potato tubers is affected by damage caused by Diabrotica speciosa, whose larvae create holes on the tubers’ skin and internal feeding tunnels. The estimation of potato tuber damage is usually performed by assessing the external damage to the detriment of feeding tunnels caused by larvae. Thus, we propose a method to estimate the damage caused by D. speciosa larvae, considering the external and internal aspects of the tubers separately. For that, potato plants cv. Agata were grown under different infestations of larvae, measuring the area occupied by the holes and the volume of internal feeding tunnels, relating these data to the total area and volume of the tuber. The methodology used allowed us to characterize an increase in damage in tubers with the highest infestation of larvae. The correlation between internal and external damage caused by D. speciosa larvae was not significant, indicating that external damage alone is not an adequate parameter for the diagnosis of overall tuber quality. However, the method proposed here provides information regarding the volume of pulp consumed by the larvae, the extent of the galleries formed, and the relative volume of damage concerning the total tuber. Moreover, the method proposed here contemplates a more precise analysis of the external area damaged by herbivory relative to the total area of the tuber, which is not commonly considered in studies of underground plant structures.